Evolution of Physico-Mathematical Models in Radiobiology and their Application in Ionizing Radiation Therapies - Garzón, O.; Plazas, M.C.; Salazar, E. J. (TECCIENCIA, 2014)
Radiobiology is the science of studying the interaction between radiation and biological tissues and the effects of the first on the latter. In this paper, we present various Physico-Mathematical models used in Radiobiology, which have been developed in order to compare and quantify the effectiveness of different radiation regimens. Different researchers have developed empirical models based on experimental considerations and on a radiological foundation. In one application of ionizing radiation therapies, the studies were able to relate several important parameters, such as dose per fraction, total dose, and the treatment time needed to obtain a better therapeutic index. In this paper, we aim to describe and discuss a number of radiobiological aspects of the results obtained throughout past research, such as Isoeffect Curves, Nominal Standard Dose (NDS), time-dose fractionation factors (TDF), and cell survival curves. Finally, we analyze the Linear- Quadratic Model.